DEVELOPMENT OF CARBON TETRACHLORIDE-INDUCED CHRONIC HEPATOTOXICITY MODEL IN RATS AND ITS APPLICATION IN EVALUATION OF HEPATOPROTECTIVE ACTIVITY OF SILYMARIN - Shah, Gopi H; Patel, Bharat G; Shah, Gaurang B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the present work is to develop carbon tetrachloride (CCl4)-induced chronic hepatotoxicity model in rats and its applicationin evaluation of hepatoprotective activity of silymarin. Methods: Animals were divided into four groups. Three groups were the disease induction group and 4th was the treatment group. In disease inductiongroups, chronic liver injury was induced by administration of CCl4 through intraperitoneal route (1 ml/kg) for 7-8 weeks. For treatment Group, 1 mlsilymarin suspension (orally) and CCl4 was given for 7-8 weeks. During disease induction and treatment period (7-8 weeks), blood samples werecollected and serum was separated which in turn used to analyze liver function tests such as serum glutamate oxaloacetate transaminase (SGOT),serum glutamate pyruvate transaminase (SGPT), alkaline phosphate (ALP), direct bilirubin, total protein (TP), and albumin (Alb) levels. Along withliver functional tests, tests to check cholesterol, glucose, and malondialdehyde (MDA) were also performed. Liver fibrosis and cirrhosis was quantifiedby histopathological studies of small portion of the excised liver. Model was validated by repetition of the experiment. Intermediate dissection wascarried out to measure an extent of liver damage. Result: Serum SGOT, SGPT, ALP, and direct bilirubin were found to be significantly higher in CCl4 intoxicated rats. TP and Alb were decreased, andMDA was found to be significantly higher in CCl4 intoxicated rats, which is the main end product of lipid peroxidation. Whereas in the treatment groupsilymarin improved the liver functions in CCl4 toxicated drug. Conclusion: We conclude that protein oxidation may play a role in the pathogenesis of CCl4 induced liver injury. The accumulation of oxidized proteinsmay be an early indication of CCl4 induced liver damage and silymarin found to be effective in liver injury by inhibiting protein oxidation.